Drugs & Crime - Irwin, Darrell (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In addressing alcohol and drug use, students should educate themselves on a variety of issues. Drug use and crime perpetuate one another, but their relationship is influenced by a wide range of psychological, pharmacological, social, and economic factors. Yet, all drug use takes place within a social context or setting and, thus, can be studied using a sociological perspective. Understanding the drug-crime nexus requires the specific investigation of these different factors. This course focuses on the nature of drug use and its connection to policing, laws, and crime. Additional issues that will be addressed are the topics of drug prevention, treatment, and addiction.